Methods of using Interactive Methods in Teaching the Topic of Symmetry - G. X. Qaypnazarova (Researchparks Publishing, 2021)
The article deals with the methods of organizing the topic related with the symmetry in the school geometry course using new pedagogical technologies. The topic of symmetry using blitz-question method is considered, its functions and convenience are described.